Preparation method of oily diaphragm

By using water mist pretreatment technology during the preparation of oily separators to form synthetic rubber in a micro-precipitated state and then rapidly drying it, the problem of reduced adhesion between the electrode and the separator is solved, the porosity and adhesion of the separator are improved, and the safety and electrochemical performance of the battery are enhanced.

CN120978334APending Publication Date: 2025-11-18HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510923099.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-04
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing oily separators are prone to reduced adhesion between the electrode and the separator when wetted by electrolyte, which affects battery safety performance. Traditional coating methods are difficult to form pores.

Method used

A water mist pretreatment technology is used to spray water mist onto the coating surface to induce micro-precipitation of the synthetic rubber. The coating is then rapidly dried to form pores. Hydrogenated nitrile rubber and polyurethane elastomer are used as the main materials. The water mist parameters and drying time are controlled to ensure porosity and adhesion.

Benefits of technology

It improves the porosity, ionic conductivity, liquid absorption rate, and adhesion of the oily separator, thereby enhancing the battery's safety and electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120978334A_ABST
    Figure CN120978334A_ABST
Patent Text Reader

Abstract

The present invention discloses an oily diaphragm preparation method, which comprises: coating at least one surface of a base membrane with a slurry, pre-treating, drying, obtaining a coating on the base membrane, and obtaining the oily diaphragm, the pre-treating comprises: maintaining for 1-4 s in a normal temperature and water vapor environment, the slurry comprises a synthetic rubber, a pore forming agent and an oily solvent, and the pore forming agent comprises a curing agent, a curing agent and a curing agent. The synthetic rubber is at least one of hydrogenated nitrile rubber and polyurethane elastomer, the particle size of the water vapor is 1.2-3.0 [mu] m, the time interval from pretreatment to drying is less than or equal to 4 s, and the volume flux of the water vapor is 20-40 mL / (s.cm < 2 >). The oily diaphragm obtained by the preparation method disclosed by the invention has relatively high porosity, ionic conductivity, liquid absorption rate, liquid retention rate and cohesive force.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of battery separators, and particularly relates to a preparation method of an oily separator. BACKGROUND

[0002] At present, with the vigorous support of the state for the development of new energy, lithium ion batteries have become an important development direction of the state, with the popularization of power batteries, the demand for power batteries is increasing, and higher requirements for the energy density and safety factor of the batteries are put forward. Therefore, a more secure battery system is needed. The battery separator, as one of the important components of the lithium battery, plays a crucial role in ensuring the safety of the battery. The oily separator is a common battery separator, and the conventional oily separator such as PVDF separator will greatly reduce the adhesion between the pole piece and the separator under the infiltration of the electrolyte. When the battery collides, the pole piece and the separator are easily dislocated and short-circuited, thereby reducing the safety performance of the battery.

[0003] In the preparation process of the oily separator, the material that can both bond the pole piece and not reduce the adhesion between the pole piece and the separator under the infiltration of the electrolyte is generally hydrogenated nitrile rubber and polyurethane elastomer (polyurethane rubber). However, when using the traditional coating method, it is difficult for hydrogenated nitrile rubber and polyurethane elastomer to form pores, mainly because the rubber precipitated during water washing and curing quickly bonds together. Therefore, improvement is urgently needed. SUMMARY

[0004] In view of the deficiencies of the prior art, the purpose of the present application is to provide a preparation method of an oily separator.

[0005] Another purpose of the present application is to provide an oily separator obtained by the above preparation method.

[0006] The purpose of the present application is achieved by the following technical solutions.

[0007] A preparation method of an oily separator, comprising: coating a slurry on at least one side of a base film, pretreating, drying, obtaining a coating layer on the base film, and obtaining an oily separator, wherein the pretreating comprises: maintaining (staying) for 1-4 s in a normal temperature and water mist (liquid water is converted into small water droplets and dispersed into air to form a water mist) environment, the slurry comprises: synthetic rubber, pore-forming agent and oily solvent, and the mass fraction ratio of the synthetic rubber, pore-forming agent and oily solvent is (0.95-6.8):(5-15):(78.2-94.05), the synthetic rubber is at least one of hydrogenated nitrile rubber and polyurethane elastomer, the particle size of the water mist is 1.2-3.0 pm, the time interval from the end of pretreatment to the start of drying is less than or equal to 4 s, and the volume flux of the water mist is 20-40 mL / (s·cm 2 ).

[0008] In the above technical solution, the oily solvent is acetone.

[0009] In the above technical solution, the drying temperature is 40-80℃.

[0010] In the above technical solution, the pore-forming agent is at least one of dimethyl carbonate and cyclohexane.

[0011] In the above technical solution, the thickness of the coating on one side is 2 to 4 μm.

[0012] In the above technical solution, the coating method is dip coating.

[0013] In the above technical solution, the method for obtaining the slurry includes: mixing synthetic rubber, pore-forming agent and oily solvent until uniform to obtain the slurry.

[0014] In the above technical solution, the polyurethane elastomer is a thermoplastic polyurethane elastomer.

[0015] In the above technical solution, the method for obtaining the slurry includes the following steps:

[0016] Step 1: Mix synthetic rubber and oily solvent until homogeneous to obtain a first solution. The ratio of synthetic rubber to oily solvent by mass is (0.95~6.8):(78.2~94.05).

[0017] In step 1, the synthetic rubber and oily solvent are mixed and stirred at 30–50°C until homogeneous to obtain the first solution. The stirring speed is 30–50 r / min, and the stirring time is 30–50 min.

[0018] Step 2: Mix the first solution and the pore-forming agent until homogeneous to obtain a slurry. By mass, the ratio of synthetic rubber to pore-forming agent in the first solution is (0.95-6.8):(5-15).

[0019] In step 2, the first solution and the pore-forming agent are mixed and stirred at 30–50°C until homogeneous to obtain a slurry. The stirring speed is 30–50 r / min, and the stirring time is 30–50 min.

[0020] The oily diaphragm obtained by the above preparation method.

[0021] Uses of water mist in improving the porosity, ionic conductivity, liquid absorption, liquid retention, or adhesion of oily membranes.

[0022] The coating containing synthetic rubber is placed in a water mist environment for 1-4 seconds to induce micro-precipitation of the synthetic rubber. Drying is then carried out within 4 seconds after the spraying stops, allowing the moisture, pore-forming agent, and oily solvent in the diaphragm to evaporate directly and rapidly. At this time, the micro-precipitated synthetic rubber solidifies directly, thus achieving pore formation.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0024] This invention involves coating a slurry containing synthetic rubber onto a diaphragm, followed by spraying (water mist) the coating surface. This allows the oily solvent in the coating to absorb a small amount of water, causing the synthetic rubber on the diaphragm to undergo a micro-precipitation state. Although the rubber molecular chains are highly flexible and mobile, the synthetic rubber on the diaphragm surface remains in a flowable micro-precipitated state. Drying is then performed within 4 seconds of stopping the spraying, allowing the water, pore-forming agent, and oily solvent in the diaphragm to evaporate rapidly. The micro-precipitated synthetic rubber then solidifies, achieving pore formation. The oily diaphragm obtained by this method exhibits high porosity, ionic conductivity, liquid absorption rate, liquid retention rate, and adhesion. Attached Figure Description

[0025] Figure 1 A scanning electron microscope image of the surface of the oily diaphragm prepared in Example 1;

[0026] Figure 2 A scanning electron microscope image of the surface of the oily diaphragm prepared in Comparative Example 2;

[0027] Figure 3 A scanning electron microscope (SEM) of the surface of the oily diaphragm prepared in Comparative Example 6;

[0028] Figure 4 This is a schematic diagram of the apparatus used to prepare the oily diaphragm in Examples 1-3. Detailed Implementation

[0029] The technical solution of the present invention will be further described below with reference to specific embodiments.

[0030] Hydrogenated nitrile butadiene rubber: Guangzhou Keen Materials Co., Ltd., number average molecular weight of 700,000; Polyurethane elastomer (thermoplastic polyurethane elastomer, TPU): Guangzhou Keen Materials Co., Ltd., number average molecular weight of 120,000; PVDF: Kureha Chemicals, Japan, weight average molecular weight of 950,000; Dimethyl carbonate: Dongguan Shilihe Biotechnology Co., Ltd.; Cyclohexane: Dongguan Shilihe Biotechnology Co., Ltd.

[0031] In the following examples, the base film is a PE film with a thickness of 7 μm.

[0032] Coating adhesion: Cut a diaphragm 30mm wide and 200mm long, attach 3M tape to the coating surface of the diaphragm as a sample, press the sample three times at a uniform speed using a standard roller, and use a tensile tester to tear one end of the 3M tape at a speed of 100mm / min to perform a peel test (peel angle of 180°) to obtain the coating adhesion.

[0033] The adhesion between the positive electrode and the separator (adhesion between the positive electrode and the separator under electrolyte immersion): The separator was cut into 25mm*150mm pieces, and the positive electrode was cut into 25mm*60mm pieces. The cut positive electrode was placed on top of the separator coating and placed in a hot press for 1 second. The hot press parameters were set as follows: pressure 1000KG, temperature 80℃. After hot pressing, the sample was immersed in electrolyte for 4 hours to obtain the electrolyte-immersed sample. Then, a peel test was performed by tearing one end of the separator in the sample at a speed of 100mm / min (peel angle 180°) to obtain the adhesion between the positive electrode and the separator. The positive electrode material in the positive electrode is lithium iron phosphate.

[0034] The adhesion between the negative electrode and the separator is tested using a method that is essentially the same as that for the adhesion between the positive electrode and the separator, except that the "positive electrode" is replaced with the "negative electrode". The negative electrode material in the negative electrode is graphite.

[0035] Liquid absorption rate: Cut a 5cm*5cm diaphragm, weigh it, and record the weight as the mass before soaking (g). Soak it in the electrolyte for 30 minutes, take it out and weigh it, and record the mass after soaking (g). Calculate the liquid absorption rate by ((mass after soaking - mass before soaking) / mass before soaking)*100%. Liquid retention rate: Take out the diaphragm that has been soaked in the electrolyte for 30 minutes and hang it for 30 minutes. Weigh it and record the mass of the liquid-retaining diaphragm (g). Calculate the liquid retention rate by ((mass of the liquid-retaining diaphragm - mass before soaking) / mass before soaking)*100%.

[0036] Ionic conductivity: tested at 25℃ and 10RH%.

[0037] The implementation principle of this invention:

[0038] In existing technology, a slurry containing synthetic rubber is coated onto a diaphragm. When the diaphragm is washed and cured in water, the pore-forming agent and oily solvent in the coating quickly dissolve into the water. The synthetic rubber that has just precipitated in water has strong flexibility and mobility due to the high degree of molecular chain flexibility. This allows the newly precipitated rubber molecules to easily diffuse and penetrate upon contact with each other on the diaphragm surface, causing the precipitated synthetic rubber to adhere together instantly. Microscopically, the synthetic rubber appears aggregated. This invention primarily improves upon the precipitation stage. After coating the slurry containing synthetic rubber onto the diaphragm, the surface of the coating is first sprayed (water mist sprayed) to allow the solvent on the coating to absorb a small amount of water, creating a micro-precipitation state for the synthetic rubber on the diaphragm. At this point, although the rubber molecular chains are highly flexible and mobile, the synthetic rubber on the diaphragm surface remains in a flowable micro-precipitated state, making it difficult to diffuse and penetrate. Then, within 4 seconds of stopping the spraying, drying is performed, allowing the water, pore-forming agent, and oily solvent in the coating to evaporate rapidly. The micro-precipitated synthetic rubber then solidifies directly, achieving pore formation. Both oil-based solvents and pore-forming agents are organic solvents and are miscible. Oil-based solvents are more polar and can dissolve synthetic rubber, but pore-forming agents are less polar and cannot dissolve synthetic rubber. When the three substances are mixed together, the synthetic rubber is dissolved in the oil-based solvent, while the pore-forming agent is dispersed in the dissolved rubber as a mixture. The pore-forming agent occupies the internal space of the dissolved rubber. When the oil-based solvent and the pore-forming agent evaporate together, the synthetic rubber solidifies and takes shape. Because of the space occupied by the pore-forming agent, many pores are left inside the synthetic rubber after evaporation.

[0039] In Examples 1-3, the oily diaphragm was prepared using the following methods: Figure 4 The device shown, Figure 4 The device, from bottom to top, includes: an immersion coating tank, a spray box, and a forced-air heating oven. The spray box and the forced-air heating oven are seamlessly connected. Sprayers are installed on both sides of the spray box to spray water mist. The sprayers are installed vertically along the spray box, and their vertical length can be changed to adjust the spraying time. Heating pipes are installed on both sides of the forced-air heating oven. During the preparation process, the slurry is added to the immersion coating tank. The base film is pulled into the slurry in the immersion coating tank by the traction roller. After coating, it is pulled into the spray box for pretreatment by the traction roller. Finally, it is pulled into the forced-air heating oven for drying by the traction roller.

[0040] Example 1

[0041] A method for preparing an oily diaphragm includes: applying a slurry to both sides of a base membrane by dip coating (the thickness of the coating is controlled by a scraper roller); pretreating the coating in a spray box at room temperature; and then drying the coating in a forced-air heating oven at 40°C for 10 seconds, thereby obtaining a coating on both sides of the base membrane to obtain an oily diaphragm. The pretreatment includes: maintaining the membrane at room temperature (20–25°C) under a water mist spraying environment for 1 second (the holding time is achieved by adjusting the vertical length of the sprayer in the spray box), with a water mist volume flux of 20 mL / (s·cm). 2 The average particle size of the water mist was 1.2 μm. The membrane ran at a speed of 50 m / min throughout the preparation process, and the time interval between stopping the water mist spraying and starting the drying process was 4 s. The air inlet frequency of the forced-air heating oven was 20 Hz.

[0042] The method for obtaining the above-mentioned slurry includes the following steps:

[0043] Step 1: Mix synthetic rubber and oily solvent, stir at 30°C and 30 r / min for 30 min until homogeneous to obtain the first solution. The synthetic rubber is hydrogenated nitrile rubber, and the oily solvent is acetone. The ratio of synthetic rubber to oily solvent by mass is 0.95:94.05.

[0044] Step 2: Mix the first solution and the pore-forming agent, and stir at 30°C and 30 r / min for 30 min until homogeneous to obtain a slurry. By mass, the ratio of synthetic rubber to pore-forming agent in the first solution is 0.95:5, and the pore-forming agent is dimethyl carbonate.

[0045] Example 2

[0046] A method for preparing an oily diaphragm includes: applying a slurry to both sides of a base membrane by dip coating (the thickness of the coating is controlled by a scraper roller); pretreating the coating in a spray box at room temperature; and then drying the coating in a forced-air heating oven at 60°C for 20 seconds, thereby obtaining a coating on both sides of the base membrane to obtain an oily diaphragm. The pretreatment includes: maintaining the membrane at room temperature under a water mist spraying environment for 3 seconds (achieved by adjusting the vertical length of the sprayer in the spray box), with a water mist volume flux of 30 mL / (s·cm). 2 The average particle size of the water mist was 2.3 μm, and the membrane operating speed was 50 m / min throughout the preparation process. The time interval between stopping water mist spraying and starting drying was 3 seconds. The air inlet frequency of the forced-air heating oven was 25 Hz.

[0047] The method for obtaining the above-mentioned slurry includes the following steps:

[0048] Step 1: Mix synthetic rubber and oily solvent, stir at 40°C and 45 r / min for 45 min until homogeneous to obtain the first solution. The synthetic rubber is polyurethane elastomer, and the oily solvent is acetone. The ratio of synthetic rubber to oily solvent by mass is 4.5:85.5.

[0049] Step 2: Mix the first solution and the pore-forming agent, and stir at 40°C and 45 r / min for 40 min until homogeneous to obtain a slurry. The pore-forming agent is cyclohexane. By mass, the ratio of synthetic rubber to pore-forming agent in the first solution is 4.5:10.

[0050] Example 3

[0051] A method for preparing an oily diaphragm includes: applying a slurry to both sides of a base membrane by dip coating (the thickness of the coating is controlled by a scraper roller); pretreating the coating in a spray box at room temperature; and then drying the coating in a forced-air heating oven at 80°C for 25 seconds, thereby obtaining a coating on both sides of the base membrane to obtain an oily diaphragm. The pretreatment includes: maintaining the membrane at room temperature under a water mist spraying environment for 4 seconds (achieved by adjusting the vertical length of the sprayer in the spray box), with a water mist volume flux of 40 mL / (s·cm). 2 The average particle size of the water mist was 3.0 μm, and the membrane operating speed was 50 m / min throughout the preparation process. The time interval between stopping water mist spraying and starting drying was 2 seconds. The air inlet frequency of the forced-air heating oven was 30 Hz.

[0052] The method for obtaining the above-mentioned slurry includes the following steps:

[0053] Step 1: Mix the synthetic rubber and the oily solvent, and stir at 50°C and 50 r / min for 50 min until homogeneous to obtain the first solution. The ratio of synthetic rubber to oily solvent by mass is 6.8:78.2. The oily solvent is acetone. The synthetic rubber is a mixture of hydrogenated nitrile rubber and polyurethane elastomer. The ratio of hydrogenated nitrile rubber to polyurethane elastomer by mass is 1:1.

[0054] Step 2: Mix the first solution and the pore-forming agent, and stir at 50°C and 50 r / min for 50 min until homogeneous to obtain a slurry. The pore-forming agent is dimethyl carbonate. By mass, the ratio of synthetic rubber to pore-forming agent in the first solution is 6.8:15.

[0055] Comparative Example 1

[0056] A method for preparing an oily diaphragm is basically the same as that in Example 1, except that "hydrogenated nitrile rubber" is replaced with "PVDF".

[0057] Comparative Example 2

[0058] A method for preparing an oily diaphragm includes: coating a slurry onto both sides of a base membrane using two coating heads of a double-sided anilox roller coater; after coating, directly coagulating the slurry in deionized water at 25°C (i.e., water washing and solidification, extraction); then sequentially passing the membrane through a first hot roller at 70°C, a second hot roller at 70°C, a third hot roller at 65°C, and a fourth hot roller at 40°C for drying; and finally winding the membrane to obtain the oily diaphragm. The diaphragm is drawn by a traction roller to complete the above preparation process at a speed of 60 m / min. The anilox roller has a cell depth of 3 micrometers.

[0059] The method for obtaining the slurry used in Comparative Example 2 includes: mixing synthetic rubber (hydrogenated nitrile rubber), pore-forming agent (dimethyl carbonate) and oily solvent (acetone), and stirring at 50°C and 30 r / min for 40 min until homogeneous to obtain the slurry. The ratio of synthetic rubber, oily solvent and pore-forming agent by mass parts is 0.95:94.05:6.65.

[0060] Comparative Example 3

[0061] A method for preparing an oily diaphragm is basically the same as in Example 1, except that: the volumetric flux of the water mist is 20 mL / (s·cm). 2 Replace “)” with “The volumetric flux of the water mist is 70 mL / (s·cm)” 2 )".

[0062] Comparative Example 4

[0063] A method for preparing an oily diaphragm is basically the same as in Example 1, except that: the volumetric flux of the water mist is 20 mL / (s·cm). 2 Replace “)” with “The volumetric flux of the water mist is 5 mL / (s·cm)” 2 )".

[0064] Comparative Example 5

[0065] A method for preparing an oily diaphragm is basically the same as in Example 1, except that the time interval from stopping spraying to starting drying is 4 seconds is replaced with the time interval from stopping spraying water mist to starting drying is 7 seconds.

[0066] Comparative Example 6

[0067] A method for preparing an oily diaphragm is basically the same as in Example 1, except that "the particle size of the water mist is 1.2 μm" is replaced with "the particle size of the water mist is 5 μm".

[0068] Figure 1 A scanning electron microscope was used to examine the surface of the oily diaphragm prepared in Example 1. Figure 1It can be seen that the oily diaphragm prepared in Example 1 has a large number of pores.

[0069] Figure 2 For the surface scanning electron microscope of the oily diaphragm prepared in Comparative Example 2, from... Figure 2 It can be seen that the pores on the surface of the oily diaphragm prepared in Comparative Example 2 are covered. This is because when the diaphragm is washed and cured in water, the oily solvent in the coating will quickly dissolve into the deionized water. This causes the rubber molecules that have just precipitated in the deionized water to diffuse and penetrate into each other on the diaphragm surface after contact, which in turn causes the rubber to adhere together instantly, and the pores are covered.

[0070] Figure 3 For the surface scanning electron microscopy of the oily diaphragm prepared in Comparative Example 6, from... Figure 3 It can be seen that the oily diaphragm prepared in Comparative Example 6 has a serious pitting phenomenon. This is because when the sprayed water mist has a large particle size, the water mist will condense together before entering the diaphragm surface, forming larger water droplets, which makes the water absorbed by the diaphragm surface uneven, resulting in a serious pitting phenomenon in the diaphragm.

[0071] The thickness, coating adhesion, air permeability and porosity of the oily diaphragms prepared in Examples 1-3 and Comparative Examples 1-6 are shown in Table 1.

[0072] Table 1

[0073]

[0074]

[0075] As shown in Table 1, the coating adhesion of the oily diaphragms prepared in Examples 1-3 remained above 100 N / m, and the porosity also reached above 45%, while the porosity of the water-washed curing method in Comparative Example 2 was only 16%. The volumetric flux of the water mist in Comparative Examples 3 and 4 was between 20 and 40 mL / (s·cm). 2 The range is too small to allow the membrane surface to form good pores, resulting in a low porosity.

[0076] Comparing Comparative Example 5 with Example 1, it can be seen that the time interval between stopping the spraying of water mist and starting the drying process should be controlled within 4 seconds to allow the diaphragm to produce better pores. If this time is exceeded, the porosity of the diaphragm will decrease and the air permeability will increase.

[0077] Comparing Comparative Example 6 with Example 1, it can be seen that when the particle size of the sprayed water mist is larger, the porosity of the diaphragm will be reduced.

[0078] The adhesion strength between the positive electrode and the separator and the negative electrode and the separator of the oily separators prepared in Examples 1-3 and Comparative Examples 1-6 are shown in Table 2.

[0079] Table 2

[0080]

[0081] As shown in Table 2, after soaking in the electrolyte, the adhesion between the positive electrode and the separator, and between the negative electrode and the separator, of the oily separators prepared in Examples 1-3 remained relatively high. The adhesion between the positive electrode and the separator, and between the negative electrode and the separator, of the oily separator prepared in Comparative Example 1 was 0 N / m, indicating that PVDF had lost its ability to bond the electrodes under electrolyte immersion. The adhesion between the positive electrode and the separator, and between the negative electrode and the separator, of the oily separator obtained in Comparative Example 2 was relatively low. This is because the traditional coating method cannot form three-dimensional pores, resulting in a smaller contact area with the separator and thus lower adhesion. The adhesion between the positive electrode and the separator, and between the negative electrode and the separator, of the oily separators prepared in Comparative Examples 3-6 was also relatively low, indicating that the volumetric flux of the water mist, the time interval between stopping the water mist spraying and starting drying, and the particle size of the water mist all have a certain impact on the bonding performance.

[0082] The liquid absorption rate and liquid retention rate of the oily diaphragms prepared in Examples 1-3 and Comparative Examples 1-6 are shown in Table 3.

[0083] Table 3

[0084]

[0085] As can be seen from Table 3, the oily diaphragm prepared in Example 1 has the best liquid absorption rate and liquid retention rate.

[0086] The impedance and ionic conductivity of the oily membranes prepared in Examples 1-3 and Comparative Examples 1-6 are shown in Table 4.

[0087] Table 4

[0088]

[0089]

[0090] As can be seen from the data in Table 1, the oily separators prepared in Examples 1-3 have more pores and higher porosity, which makes them more capable of adsorbing electrolyte and facilitates the shuttle movement of lithium ions within the separator. This results in higher ionic conductivity, increasing the charge and discharge efficiency of the battery. This also corresponds to the ionic conductivity and impedance data in Table 4. Comparative Example 2 used a traditional coating method, which resulted in poor pore formation and severe pore blockage, leading to an ionic conductivity close to 0 mS / cm.

[0091] The present invention has been described above by way of example. It should be noted that any simple modifications, alterations or other equivalent substitutions that can be made by those skilled in the art without creative effort without departing from the core of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing an oily diaphragm, comprising: A slurry is coated onto at least one side of a base membrane, pretreated, and dried to obtain a coating on the base membrane, resulting in an oily separator. The pretreatment includes maintaining the membrane in a water mist environment at room temperature for 1–4 seconds. The slurry comprises synthetic rubber, a pore-forming agent, and an oily solvent, with a mass ratio of (0.9–7):(5–15):(78–95). The water mist has a particle size of 1.2–3.0 μm, the time interval from the end of pretreatment to the start of drying is ≤4 seconds, and the volumetric flux of the water mist is 20–40 mL / (s·cm). 2 ).

2. The preparation method according to claim 1, characterized in that, The oily solvent is a liquid capable of dissolving both synthetic rubber and water, and the synthetic rubber is at least one of hydrogenated nitrile butadiene rubber and polyurethane elastomer.

3. The preparation method according to claim 1, characterized in that, The pore-forming agent is at least one of dimethyl carbonate and cyclohexane.

4. The preparation method according to claim 1, characterized in that, The coating has a single-sided thickness of 2–4 μm.

5. The preparation method according to claim 1, characterized in that, The coating method is dip coating.

6. The preparation method according to claim 1, characterized in that, The drying temperature is 40–80℃.

7. The preparation method according to claim 1, characterized in that, Methods for obtaining slurry include: mixing synthetic rubber, pore-forming agent and oily solvent until homogeneous to obtain slurry.

8. The preparation method according to claim 7, characterized in that, Synthetic rubber and an oily solvent are mixed and stirred at 30–50°C until homogeneous to obtain a first solution. The first solution is then mixed with a pore-forming agent and stirred at 30–50°C until homogeneous to obtain a slurry.

9. Uses of water mist in improving the porosity, ionic conductivity, liquid absorption rate, liquid retention rate and adhesion of oily diaphragms.

10. The oily diaphragm obtained by the preparation method according to any one of claims 1 to 8.